LOEX Option: A Combination of Exchange Option and Lookback Option - Ghasem Pour, Rajabali; Pourmohammad Azizi, S.; Ahmad Waloo, Sajad (Management Analytics and Social Insights, 2024)
In this article, we consider modeling and pricing a combination of two options (Exchange option and Lookback option) that we call the LOEX option. It is a type of exotic option, or clearer, path-dependent option because its price depends on the maximum and minimum prices of the assets to be considered. In reality, we introduce a conditional claim on two assets: the holder can change the first asset with the highest price to the second with the lowest price or cancel the transaction at the strike time. In this paper, after describing and modeling this option, we use numerical methods to estimate the pricing using the MATLAB software and present the results.